Enhancing Constitutional Justice by Using External References: The European Court of Human Rights' Reasoning on the Protection against Expulsion - Farahat, Anuscheh (Leiden Journal of International Law, 2015)
This article argues that the European Court of Human Rights (ECtHR) uses external references as a tool to enhance 'constitutional justice'. This technique is illustrated by the Court's contribution to an important shift in migration law beginning in the late 1980s and resulting in an enhanced scheme for protection against expulsion in Europe. This shift reflects the changing role of the ECtHR from a court primarily concerned with providing 'individual justice' to a court aiming at enabling 'constitutional justice'. The aim of the article is to contextualize the aforementioned shift with a historical view and to understand it in methodological terms. It argues that the Court supports its dynamic interpretation of the right to privacy in Article 8 of the European Convention of Human Rights in crucial judgments by reference to often non-binding instruments issued by the Council of Europe and to other human rights treaties. In this regard, the case of protection against expulsion illustrates a particular feature of the Court's turn to 'constitutional justice', namely the increased application of the principle of systemic integration. This allowed the Court to develop a meaningful and comprehensive protection scheme in the first place. However, the article reveals that once the substantial standard developed by the ECtHR has been formally implemented in domestic law, domestic decisions are reviewed with significantly less scrutiny. This limitation may again be explained by the 'constitutional turn' which results in a pragmatic tendency to proceduralization in the jurisprudence of the ECtHR.
Keywords: Constitutionalization; European Court of Human Rights; external references; human rights law; migration law